Enhancing Salesforce Performance through Knowledge Sharing and Customer Orientation: The Mediating Role of Self-Efficacy - Muhammad Sirojuddin Amin; Alfian Budi Primanto (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study examines the influence of knowledge sharing and customer orientation on salesforce performance through the mediating role of self-efficacy among restaurant salespeople in Indonesian MSME settings, addressing the psychological mechanisms linking these antecedents to performance and the potential for overconfidence bias. Research Design & Methods: A quantitative approach used questionnaires distributed to 380 restaurant salespeople (frontliners, waiters/waitresses, and cashiers) in Malang Raya, selected through purposive and convenience sampling; data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings: Customer orientation has a positive and significant direct effect on salesforce performance, while knowledge sharing has no significant direct effect. Both knowledge sharing and customer orientation positively influence self-efficacy; however, self-efficacy negatively and significantly affects salesforce performance and negatively mediates the effects of knowledge sharing and customer orientation on performance, indicating overconfidence bias. Implications & Recommendations: Restaurant MSME management should prioritize customer orientation while carefully managing knowledge sharing programs, and must monitor and calibrate employee self-efficacy to prevent overconfidence. Training should incorporate objective feedback, realistic goal setting, and adaptive selling development so self-efficacy remains motivating rather than complacency-inducing. Contribution & Value Added: This study challenges the conventional positive assumption of Social Cognitive Theory on self-efficacy, showing empirically that self-efficacy can negatively influence performance through overconfidence bias, extending the theory into Indonesia's food and beverage MSME context and offering original empirical evidence and managerial insight.